The Effects of Cooking Process and Meat Inclusion on Pet Food Flavor and Texture Characteristics - Kadri Koppel; Michael Gibson; Sajid Alavi; Greg Aldrich (Animals, 2014)
The pet food industry is an important portion of the food and feed industries in the US. The objectives of this study were (1) to determine cooking method (baking or extrusion), meat inclusion (0 or 20%), and extrusion thermal to mechanical energy ratios (low, medium, and high) effects on sensory and volatile properties of pet foods, and (2) to determine associations among sensory and volatile characteristics of baked and extruded pet foods. Descriptive sensory analysis and gas chromatography-mass spectrometry were used to analyze the pet food samples. It was found that baked samples were lighter in color (2.0–2.6 baked vs. 3.5–4.3 extruded, color intensity scale 0–15), and had lower levels of attributes that indicated rancidity (i.e., fishy flavor; 0.3–0.6 baked, 0.6–1.5 extruded, scale 0–15), whereas extruded pet foods were more cohesive in mass, more friable, hard, and crisp, but less powdery than baked samples. Fresh meat inclusion tended to decrease bitterness and increase fishy flavor and cohesiveness of pet foods. High thermal to mechanical energy ratio during extrusion resulted in less musty and more porous kibbles. The main volatile compounds included aldehydes, such as hexanal and heptanal, ketones, and alcohols. Extruded samples did not contain methylpyrazine, while baked samples did not contain 2-butyl furan. Future studies should consider evaluating the relationship between sensory results and animal palatability for these types of foods.